Vitamin D Supplementation Improves Mitochondrial Function and Reduces Inflammation in Placentae of Obese Women - Phillips, Elysse A.; Hendricks, Nora; Bucher, Matthew; Maloyan, Alina (Frontiers in Endocrinology, 2022)
About 30% of pregnant women in the US are obese. We have reported mitochondrial dysregulations and increased inflammation in the placentae of obese women. Vitamin D (VitD) is a major player in calcium uptake and was shown to modulate mitochondrial respiration and inflammation. Studies show decreased VitD in obese individuals; however, the effect of maternal obesity on VitD metabolism and its association with placental function remains understudied. Maternal/cord blood plasma and placental samples were collected upon C-section from normal-weight (NW, body mass index (BMI)<25) and obese (OB, BMI>30) women at term. We measured 25(OH)D3 (calcidiol) levels in maternal and cord blood using ELISA. We assessed the expression of CYP27B1, an activator of calcidiol, and Vitamin D receptor (VDR) in placentae from NW and OB, and women with gestational diabetes and preeclampsia. We examined the effects of VitD supplementation on mitochondrial function and inflammation in NW/OB trophoblasts, using the Seahorse Bioanalyzer and Western blot. Vitamin D levels in blood from OB but not NW women and in cord blood from babies born to NW/OB women showed an inverse correlation with maternal BMI (r=-0.50, and r=-0.55, p<0.05). Cord plasma VitD levels showed a positive correlation with placental efficiency, i.e., the ratio between fetal and placental weight, and with maternal blood VitD levels (r=0.69 and 0.83 respectively, p<0.00). While we found no changes in CYP27B1 in OB vs. NW women, VDR expression was decreased by 50% (p<0.05). No changes in VDR were observed in the placentae of women with gestational diabetes or preeclampsia. Cytotrophoblasts from OB placentae showed an increase in VDR expression after treatment with calcitriol (10 nM and 100 nM), an active form of VitD. Trophoblasts from OB women treated with calcitriol improved mitochondrial respiration (p<0.05). We also found a two-fold increase in expression of the NLRP3 inflammasome and the pro-inflammatory cytokine IL-18 in trophoblasts from OB women, with IL-18 being reversed by calcitriol (100 nM). We show that VitD deficiency is at least partially responsible for mitochondrial dysfunction and increased inflammation in the placentae of obese women. Vitamin D supplementation could be beneficial in improving placental dysfunction in obese women.